The Pedagogies of e-Learning - Mehanna, Wassila Naamani (Proceedings of the International Conference on Networked Learning, 2004)
There is a great need for empirical examinations of e-learning environments and pedagogical assessments of online interactions and discussions. This paper reports part of the findings from a multi-case study that has analysed online conferences of four different postgraduate programmes in four different UK universities. A model of 29 pedagogical behaviours emerged from the one-year grounded analyses and then applied in analysing additional 5 million words of online interactions. The findings suggest four clusters of pedagogies correlated with students’ grades; however, the effect size calculation reveals an educational significance for all of them. This indicates if they were to be employed in online classrooms they are likely to enhance students’ learning and outcomes.